2014
DOI: 10.1158/1055-9965.epi-13-0886
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Intake and Gastric Cancer Risk: The Singapore Chinese Health Study

Abstract: Background Despite experimental evidence showing chemopreventive effects of coffee-related compounds on gastric carcinogenesis, epidemiologic studies generally do not support coffee-gastric cancer associations. Observational data are lacking among high-risk populations with sufficient regular coffee consumption. Methods We examined the association between caffeinated coffee intake and gastric cancer risk in a population-based cohort that enrolled 63,257 Chinese men and women aged 45–74 years between 1993 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 44 publications
2
25
0
1
Order By: Relevance
“…The results from this study support the growing body of evidence suggesting coffee consumption as a protective factor for CRC (11, 15, 23) and as a predictor of reduced CRC recurrence and death (24). However, there are differences in results and interpretations of case-control and cohort studies (14, 18), possibly due to the different time period of exposure considered relative to cancer diagnosis.…”
Section: Discussionsupporting
confidence: 84%
“…The results from this study support the growing body of evidence suggesting coffee consumption as a protective factor for CRC (11, 15, 23) and as a predictor of reduced CRC recurrence and death (24). However, there are differences in results and interpretations of case-control and cohort studies (14, 18), possibly due to the different time period of exposure considered relative to cancer diagnosis.…”
Section: Discussionsupporting
confidence: 84%
“…The details of this case–control study have been previously reported (Ainslie-Waldman et al , 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the possibility that smoking is responsible for the observed positive association merits further considerations because of the strong correlation between coffee consumption and cigarette smoking [10,12]. This possibility was somewhat supported by the results from Singapore Chinese Health Study [16], in which daily coffee consumption significantly decreased gastric cancer risk in non-smokers, and non-significantly increased the risk in smokers. Despite taking into account the number of cigarettes smoked, the possibility of confounding by smoking remains because of the relatively rough measurement of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Only the Singapore Chinese Health Study [16] had taken into account the influence of helicobacter pylori (H. pylori) infection, and the results were similar before and after adjustment for H. pylori. There was one study [10] that considered filtered and boiled coffee separately, and no difference was found.…”
Section: Discussionmentioning
confidence: 99%